Feasibility Investigations on Selective Laser Melting for the Development of Microchannel Cooling in Power Electronics - Syed Khaja, Aarief Hussain; Perinan Freire, Antonio; Kästle, Christopher; Franke, Jörg (Proceedings of the 67th Electronic Components and Technology Conference (ECTC), 2017)
The introduction of new generation semiconductor materials into power electronics brings not only performance improvements but also technological challenges for the thermal management as the urge for high temperature operating power modules and packaging systems increases. The limiting factor for the performance and application range is not anymore the chip temperatures but the restrictions of the state-of-the-art packaging systems. Especially for high power applications, the temperatures can rise to more than 200 °C at the interconnect level. In this paper, as a contribution towards the above requirements, the selective laser melting (SLM) technique has been used to fabricate a heat sink concept which would not be feasible with conventional production techniques. Here the feasibility of producing a heat sink concept with SLM based on micro-cooling technology is successfully introduced and the thermal management performance is demonstrated. The advantages mainly for the volume and weight reduction along with performance improvement are highlighted.